6(2X-9)-5=6(X-4)+1

Simple and best practice solution for 6(2X-9)-5=6(X-4)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2X-9)-5=6(X-4)+1 equation:


Simplifying
6(2X + -9) + -5 = 6(X + -4) + 1

Reorder the terms:
6(-9 + 2X) + -5 = 6(X + -4) + 1
(-9 * 6 + 2X * 6) + -5 = 6(X + -4) + 1
(-54 + 12X) + -5 = 6(X + -4) + 1

Reorder the terms:
-54 + -5 + 12X = 6(X + -4) + 1

Combine like terms: -54 + -5 = -59
-59 + 12X = 6(X + -4) + 1

Reorder the terms:
-59 + 12X = 6(-4 + X) + 1
-59 + 12X = (-4 * 6 + X * 6) + 1
-59 + 12X = (-24 + 6X) + 1

Reorder the terms:
-59 + 12X = -24 + 1 + 6X

Combine like terms: -24 + 1 = -23
-59 + 12X = -23 + 6X

Solving
-59 + 12X = -23 + 6X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6X' to each side of the equation.
-59 + 12X + -6X = -23 + 6X + -6X

Combine like terms: 12X + -6X = 6X
-59 + 6X = -23 + 6X + -6X

Combine like terms: 6X + -6X = 0
-59 + 6X = -23 + 0
-59 + 6X = -23

Add '59' to each side of the equation.
-59 + 59 + 6X = -23 + 59

Combine like terms: -59 + 59 = 0
0 + 6X = -23 + 59
6X = -23 + 59

Combine like terms: -23 + 59 = 36
6X = 36

Divide each side by '6'.
X = 6

Simplifying
X = 6

See similar equations:

| 1/2+9/12 | | 3(w+13)=89 | | X^2+22x-203=0 | | 2[d-(2d+18)+13]=2(d+5) | | 16=2e | | 4(8x+32)=64 | | -5v-3+2=22 | | 9(2x-4)=3(6x+8) | | 8x+2=3x+13 | | -29=-7y-9y | | 36m^2-49/25 | | 14=24 | | 5+9t-2=9t+17-7t | | 9d+5-2d=20 | | x/6=42 | | 24=-2(6a-7) | | 3(x-0.8)=4x-4 | | 3x-21-7x+20= | | 1+2/x+5/x^2=0 | | 1/2+9/x=5/4 | | 10-2p=4q | | 12-3p=q | | 3x+16x=95 | | 7-2(1-3s)=35 | | -21+[-14+(-13)]= | | 15-p=q | | 4(4+2x)=7(x-2) | | y=20-10 | | -2p-2(4-4p)=4(p-4)-18 | | z/4=-10 | | m-1/2=-11/12+11/6m | | 36m^2-25/4 |

Equations solver categories